MODEL KELEMBAGAAN PENGEMBANGAN USAHATANI HUTAN RAKYAT GANITRI DI PROVINSI JAWA TENGAH - Idin Saepudin Ruhimat (Jurnal Hutan Tropis, 2020)
This study aims to formulate an institutional model for the development of ganitri community forest farming in Central Java Province. The study was conducted from January to December 2012 in three districts in Central Java Province, namely Cilacap, Kebumen, and Wonosobo. Data were analyzed descriptively with a qualitative approach. The results showed that the institutional model of agribusiness that optimizes the role of various parties such as government, private sector, and the community at all stages of farming such as the procurement of inputs, production, processing, and marketing can be used as an institutional model for the development of community forest ganitri both for production purposes timbers or seeds. The local government of Cilacap, Kebumen, and Wonosobo are advised to optimize aspects of mentoring, coaching, and counseling to stakeholders in the development of ganitri community forest farming and to find alternative markets and value added ganitri crops.